2009
DOI: 10.3324/haematol.2009.013680
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte transfusion therapy: randomization after all?

Abstract: MGUS outside the context of a clinical trial is not recommended because of the uncertain ratio between potential benefit and toxicity. Future studies should refine the risk factors for progression and develop criteria to identify people at high risk of progression who are candidates for preventive trials, as well as identify patients without any risk of progression who can be reassured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…GTXs have also been used prophylactically in neutropenic patients despite the absence of solid evidence to support pre-emptive utilization of donor GTXs (62, 70). However, results of the few published studies reported positive outcome but no significant difference with respect to duration of hospitalization or 100-day survival has been reported (62, 70). …”
Section: Donor Granulocyte Transfusion Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…GTXs have also been used prophylactically in neutropenic patients despite the absence of solid evidence to support pre-emptive utilization of donor GTXs (62, 70). However, results of the few published studies reported positive outcome but no significant difference with respect to duration of hospitalization or 100-day survival has been reported (62, 70). …”
Section: Donor Granulocyte Transfusion Therapymentioning
confidence: 99%
“…However, GTXs should be given in specific institutions according to well established and preferably standardized operational procedures in order to ensure safety of both donors and recipients (62). …”
Section: Donor Granulocyte Transfusion Therapymentioning
confidence: 99%
“…Nonetheless, the use of granulocyte transfusions has remained infrequent and only about 1000 granulocyte units are transfused per year in the US [1]. Recently, interest in granulocyte transfusions has increased for a variety of reasons, including the ability to collect granulocytes in higher numbers using granulocyte colony-stimulating factor (GCSF), an increased incidence of therapy-related neutropenia and a rise in antibiotic resistance [20]. Moreover, recent research suggests that granulocyte transfusions could be used as a treatment for cancer [9,15,27].…”
Section: Introductionmentioning
confidence: 99%
“…Granulocyte transfusions (GTXs) constitute a promising adjuvant therapy in case of neutropenic and immunocompromised patients in which the exclusive use of modern antimicrobial drugs is ineffective. 1,2 To acquire a sufficient number of cells for transfusion purposes the donor is treated with a combination of G-CSF and dexamethasone (dexa) before the collection of the neutrophils by leukapheresis. 3,4 Clearly, for transfusions to be beneficial it is important that the donor granulocytes are functional.…”
Section: Introductionmentioning
confidence: 99%